Doebner-type pyrazolopyridine carboxylic acids in an Ugi four-component reaction - Murlykina, Maryna V (Beilstein J Org Chem, 2019)
Substituted 1H-pyrazolo[3,4-b]pyridine-4- and 1H-pyrazolo[3,4-b]pyridine-6-carboxamides have been synthetized through a Doebner–Ugi multicomponent reaction sequence in a convergent and versatile manner using diversity generation strategies: combination of two multicomponent reactions and conditions-based divergence strategy. The target products contain as pharmacophores pyrazolopyridine and peptidomimetic moieties with four points of diversity introduced from readily available starting materials including scaffold diversity. A small focused compound library of 23 Ugi products was created and screened for antibacterial activity.